Breastfeeding, maternal psychopathological symptoms, and infant problem behaviors among low-income mothers returning to work. (September 2021) - Wu, Qiong; Farley, Tatjana; Cui, Ming
Abstract: Rationale: One of the biggest challenges for mothers returning to work after childbirth is breastfeeding. Studies documented the physical health benefits of breastfeeding for mothers and children. However, research findings concerning the longitudinal effects of breastfeeding on maternal and children's mental health are mixed. Objective: The current study investigated the longitudinal effects of the length of breastfeeding on maternal psychopathological symptoms and infants' problem behaviors, among a sample of low-income working mothers. Methods: The sample included 285 infants and their mothers (primarily minority, low-income, and single) who returned to work 3-month postpartum, recruited from an ethnically diverse and economically disadvantaged area in a southern U.S. state. Mothers' breastfeeding behaviors were assessed four times in the first year postpartum, and mothers' psychopathological symptoms and their infants' problem behaviors were reported by mothers two times, at 12-month and 24-month postpartum. Results: Path models revealed that high maternal psychopathological symptoms in infancy worsened the effect of breastfeeding on child externalizing behaviors in toddlerhood. Likewise, very high infant externalizing behaviors worsened the effect of breastfeeding on maternal hostility one year later. Conclusions: This study suggests the need for implementing prevention interventions with a lifecycle approach and continued, tailored professional breastfeeding support after hospital discharge among at-risk working mothers. Findings of this study can inform public policy by highlighting the importance of considering joint breastfeeding support and mental health counseling in the delivery of services to mothers and their infants who live in under-resourced environments and struggle with maternal psychopathology. Highlights: We studied prospective effects of breastfeeding on maternal and child mental health. Maternal symptoms worsened the effect of breastfeeding on child behavioral problem. Child behavioral problem degraded the effect of breastfeeding on maternal hostility.